EVALUASI MATERI PENDIDIKAN ISLAM PERSPEKTIF GENDER (Evaluasi Terhadap Materi Buku Ajar Agama Islam) - Syafrida - (Marwah: Jurnal Perempuan, Agama dan Jender, 2015)
Education is a tool for transferring the norms of society, knowledge and human capabilities, as well as a tool to assess and convey ideas and new values, including the values and norms of gender. It is known that many gender inequality occurred  in society are assumed to arise because there is a gender bias in education, including religious education. As an example of gender bias in the curriculum of Islam among the materials about the origin of human events, the obligation to pray in congregation, the provisions of polygamy, spousal function in marriage. In an effort to realize the religious understanding of the nature of gender, then it should be required revisions to matters of gender bias in textbooks of the Islamic religion. It should be stressed also awareness about the value of education gender perspective to all parties, especially the author and editor of books on the fact that the curriculum is not gender neutral. Meanwhile, for the religious teachers are required to be more critical and sensitive in identifying and examine all matters relating to gender inequality in the learning process that takes place in their daily work.